Pencapaian Kompetensi Kognitif Pencapaian Kompetensi Kognitif pada Pembelajaran Discovery Learning Berbantuan Lembar Kerja Siswa - Amalia, Ika Nur; Nuswowati, Murbangun; Nurhayati, Sri (Chemistry in Education, 2018)
This study is case study that aims to find out how the achievement of cognitive competence of students on salt hydrolysis material after the application of learning model discovery learning aided student worksheet. This research design uses pretest-posttest control group design. Sampling using purposive random sampling technique, which is based on the advice of subject teachers as well as considering the percentage of completeness of studentsâ semester midterms. This study used a sample class as a case study, with a research subject of 34 students. The research procedure consists of four stage: preliminary stage, preparation stage, implementation stage, and final stage. The methods used to collect data in this study include the method of documentation and test methods consisting of pretest before the implementation of learning and posttest after the implementation of learning model discovery learning. The results of the analysis on the achievement of cognitive competence shows that are there is a very significant improvement from the results of studentsâ pretest and posttest completeness. The large percentage of pretest that is equal to 22,95% while the percentage of completeness at least 85%, so it can be concluded that students have been able to achieve cognitive competence on salt hydrolysis material after applying learning discovery learning aided student worksheet.